Upartyjnienie versus personalizacja jako czynniki determinujące zachowania wyborcze w krajowych elekcjach w 2015 roku - Szczepański, Dominik (Political Preferences, 2016)
Party-dependency versus personalization as the factors determining voting behaviour in national elections in 2015 The aim of the article was to present factors that determined voting behaviour of citizens in national elections in 2015 in the perspective of party and personal attitudes of the interviewees. Except for presenting conclusions that result from the course of the research process in the aforementioned range, also the elements that could have affected eventual responses of the interviewees were indicated. These include changes at the position of PO (civic platform) leaders, appearance of new political entities (Ryszard Petru’s Nowoczesna, Together Party, Kukiz 15), or unification processes on the political right, and partially on the left. Personal conflicts and ways of conducting the campaign that could have affected attitudes of voters were also indicated. A complement to logical conclusions from the conducted research in the perspective of party and personal determinants of voting preferences were also analyses of whether election posters and billboards should be put in the areas that belong to churches. From the perspective of political options supported by citizens, and their attitudes towards the role of Church during electoral campaigns, the analysis of this phenomenon led to interesting conclusions. Key words: elections behaviour, presidential elections, parliamentary elections, personalization, electoral, Poland